Metal Pollution Indices of Surface Sediment and Water from the Upper Reaches of Sombriero River, Niger Delta, Nigeria - Howard, Ibigoni Clinton; Olulu, Briggs Amonia (Our Nature, 2013)
Metal pollution indices of the surface sediments and water of the upper reaches of Sombriero river was investigated using Absorption Spectrophotometery. The data obtained for the metals- Cd, Pb, V, Fe, Ni, Cu and Zn showed consistency in the metal pollution indices of the various stations of the study area. The stations with higher pollution indices were related to areas of intense activities. Several metal pair correlations were obtained in the surface sediments than in the surface water. Both media had Zn-Cd and Cu-Fe metal pair correlations. The pattern of the metals in the surface water at 95% significant level is Fe>Zn = Cu = Pb = N = Cd = V while that of the sediment is Fe>Zn = Cu = Ni = Pb = V = Cd. Each of the metals differed significantly between the media (P<0.05) sediment > water, indicating the former to be a better monitoring index of aquatic pollution by these metals. In comparison to other related work the degree of contamination of the upper reaches of the Sombriero River is low but a gradual enrichment of these pollutants could have a deleterious effect on the aquatic resources of the area and the consumers thereof. DOI: http://dx.doi.org/10.3126/on.v10i1.7783